2020
DOI: 10.3390/ijms21020575
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-Based Evidence for a Pro-Oncogenic Role of ESRP1 in Human Colorectal Cancer Cells

Abstract: The RNA-binding protein, Epithelial Splicing Regulatory Protein 1 (ESRP1) can promote or suppress tumorigenesis depending on the cell type and disease context. In colorectal cancer, we have previously shown that aberrantly high ESRP1 expression can drive tumor progression. In order to unveil the mechanisms by which ESRP1 can modulate cancer traits, we searched for proteins affected by modulation of Esrp1 in two human colorectal cancer cell lines, HCA24 and COLO320DM, by proteomics analysis. Proteins hosted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…There was marked PI3K/AKT pathway activation and SNAI1 protein overexpression, which skewed the cells towards adopting a partially mesenchymal, and more tumorigenic, molecular profile. These data were further supported by proteomics data on ESRP1-modulated CRC cells [12]. The observation that ESRP1 can have pro-tumorigenic and pro-metastatic activities was also shown by other studies [13][14][15].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…There was marked PI3K/AKT pathway activation and SNAI1 protein overexpression, which skewed the cells towards adopting a partially mesenchymal, and more tumorigenic, molecular profile. These data were further supported by proteomics data on ESRP1-modulated CRC cells [12]. The observation that ESRP1 can have pro-tumorigenic and pro-metastatic activities was also shown by other studies [13][14][15].…”
Section: Introductionsupporting
confidence: 75%
“…The CRC cell lines used in this study had been previously characterized, at both the genomic and transcriptomic level, and authenticated [19]. COLO320DM cells were cultured in RPMI (ThermoFisher Scientific, Monza, Italy), 10% FBS and penicillin/streptomycin (PS), while HCA24 and Caco-2 cells were kept in DMEM, 10% FBS and PS as previously described [12]. ESRP1 expression was modulated with shRNA cloned into pLKO.1 lentiviral vector for stable knockdown and with human ESRP1 ORF cloned into pLX304 lentiviral vector for stable overexpression [11].…”
Section: Cell Lines and Esrp1 Expression Modulationmentioning
confidence: 99%
“…Epithelial splicing regulatory protein-1 (ESRP1) that signals through oncogenic MAPK signaling pathway is also differentially dysregulated in EpKS compared to EnKS patients. ESRP1 has been shown to support anchorage-independent growth of colorectal cancer cells and promote metastasis formation in vitro [67,68]. It also supports mesenchymal to epithelial transition in ovarian cancer cells [69].…”
Section: Hiv-1 Indirectly Promotes Ks Development/maintenancementioning
confidence: 99%
“… Tan et al (2012) used the colon cancer cell line, HCT-116, to identify Stathmin-1 as a protein biomarker of cancer cell migration. Ala et al (2020) identified the pro-oncogenic role of ERSP1 in the colorectal cell lines HCA24 and COLO320DM. Hu et al (2018) used HCT-116 and RKO, selectively cultured to be highly invasive, to identify the Cdc42-Cdc42BPA signaling pathway as a marker for colon cancer invasion.…”
Section: D Cell Culturementioning
confidence: 99%